2017
DOI: 10.1002/smj.2666
|View full text |Cite
|
Sign up to set email alerts
|

Interorganizational Imitation and Acquisitions of High‐tech Ventures

Abstract: Research summary: This article shows that there is a positive association between the changes in the number of prior acquisitions or the changes in the prominence of prior acquirers within the focal venture's subfield and the venture's likelihood to be acquired. Results are in line with the existence of frequency‐ and trait‐based imitation in acquisitions targeting tech ventures. More importantly, these positive associations are more pronounced when (a) exogenous technological uncertainty within the venture's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 95 publications
(182 reference statements)
1
20
0
Order By: Relevance
“…Chen et al (2011) reported that mimetic pressures (frequency-based and outcome-based imitation) are important determinants of green IT adoption. Recently, Ozmel et al (2017) examined and confirmed the positive effects of frequency-based imitation and trait-based imitation on acquisitions of ventures.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
See 1 more Smart Citation
“…Chen et al (2011) reported that mimetic pressures (frequency-based and outcome-based imitation) are important determinants of green IT adoption. Recently, Ozmel et al (2017) examined and confirmed the positive effects of frequency-based imitation and trait-based imitation on acquisitions of ventures.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…Haunschild and Miner (1997) classified inter-organizational imitation as three types – frequency-based imitation (imitating common practices), trait-based imitation (imitating practices of firms with certain features) and outcome-based imitation (imitating practices of firms with certain outcomes). Inter-organizational imitation has been applied in various research fields, such as entering new product or geographic markets (Belderbos et al , 2011; Fernhaber and Li, 2010), IT adoption (Chen et al , 2011), IT outsourcing (Hanafizadeh and Zare Ravasan, 2018) and acquisition of high-tech ventures (Ozmel et al , 2017; Yigitbasioglu, 2015). For example, Fernhaber and Li (2010) explored the impact of inter-organizational imitation on new venture international entry and performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Target selection has also been argued to be influenced by managers observing other M&As taking place in a related business domain (Ozmel et al, 2017) or by performance feedback (Kumar et al, 2015).…”
Section: Target Selectionmentioning
confidence: 99%
“…Baum et al (2000) suggest that experiential-learning processes lead firms to select targets that are geographically and organizationally similar to their most recent targets, whereas vicarious-learning processes lead acquirers to favor targets that are similar to the M&A targets of their peers. Target selection has also been argued to be influenced by managers observing other M&A taking place in a related business domain (Ozmel, Reuer, & Wu, 2017) or by performance feedback (Kumar, Dixit, & Francis, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, it has seldom considered the possible influence of inter-organizational relationships on expatriate assignment. Firms are not only affected by their own resources and ownership structure, they can also be influenced by what other firms do (Greve 2011;Guillén 2002;Haunschild and Miner 1997;Ozmel et al 2017;Xie and Li 2017), including in forming their expatriation strategies (Williamson and Cable 2003). The neo-institutional theory suggests that firms tend to imitate their peers' practice, which is considered legitimate (DiMaggio and Powell 1983;Haunschild and Miner 1997;Meyer and Rowan 1977).…”
Section: Introductionmentioning
confidence: 99%